In Memoriam Doctora Juana María Coha Gonzáles (1926-2017) - Alvarado Iparraguirre, Débora (2019)
Dr. Juana María Coha was a professor at the Universidad Nacional Mayor de San Marcos, recognized for her inner energy and intense personality, which could be perceived in her courses and in particular in conversations with her students. With a great desire to promote research and solve problems in the country, it became the guide of many promotions of microbiologists. Juana María Coha Gonzáles, was born on June 24, 1926 in the city of Huacho and died on July 22, 2017. These lines are written by her students and disciples that we continue what she forged in her lines of research.